PERKEMBANGAN, EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA TEGAL (Students' Journal of Accounting and Banking, 2013)
This study was conducted to determine how much progress, effectiveness and contribution of local taxes and local retribution to local own revenues. Population and sample from the tasted is tegal city. This test use realist local own revenues, realist local taxes, and realist local retribusion from 2009-2012. The data’s get from Dinas Pendapatan Keuangan Aset Daerah (DPKAD) Tegal City. Analysis from inflate to be found autenthic area Tegal City from 2009-2012 to reach for 33.62 percent. Inflate of tax area Tegal City from 2009-2012 to reach for 40.03 percent, inflate of retribution area Tegal City from 2009-2012 to reach for 40.48 percent. Efectivity to local own revenues Tegal City from 2009-2012 to reach for 110.95 percent. Efectivity local taxes Tegal city 2009-2012 for 116.46 percent. Efectivity local retribution area Tegal city 2009-2012 to reach for 110.95 percen. Acceptance contribusion local tax to local own revenues Tegal city 2009-2012 compeletely high 18.67 percent. Acceptance contribution retribution to local own revenues Tegal city 2009-2012 to reach for 12.26 percen. To step on achieve total local own revenues and flow achieve local government Tegal city have to do to collect tax area kind and retribution area according to UU No. 28 year 2099 with fixed area rules as basic to rule to collect. Keywords: Local Own Revenues, Local Tax, Local Retribution